ANALYSIS OF THE ROLE OF THE DRY DOCK IN THE SEAWORTHINESS OF THE KM. SIRIMAU - Jesica Flora Ameliya Dae; Eva Susanti P (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ship seaworthiness is a fundamental requirement for ensuring the safety and reliability of maritime transportation. Dry docking plays an essential role in ship maintenance by providing an opportunity to identify and repair technical deficiencies that may affect a vessel's operational condition. This study aims to analyze the role of dry dock operations in supporting the seaworthiness of KM Sirimau, with particular emphasis on addressing leakage in the No. 41 port ballast tank top plate and the dimensional mismatch between the anchor chain and the gypsy. This research employed a descriptive qualitative method with a case study approach. Data were collected through direct observation during the dry docking process, semi-structured interviews with personnel involved in ship repairs, and the analysis of technical documents and maintenance reports. The collected data were analyzed through data reduction, data presentation, and conclusion drawing, supported by triangulation of observational, interview, and documentary evidence. The findings indicate that the dry docking process plays a significant role in identifying technical deficiencies, implementing corrective maintenance, and verifying the condition of damaged ship components. Repairs to the corroded ballast tank top plate and adjustments to the anchoring system successfully restored the operational functions of these components, thereby supporting the fulfillment of ship seaworthiness requirements. In addition, post-repair inspections and operational testing ensured that the repaired components performed in accordance with technical and operational standards. The study concludes that dry docking is an essential component of ship maintenance management, contributing to maritime safety and the operational reliability of passenger vessels.